Correlation of carbon isotope stratigraphy and paleoenvironmental conditions in the Cretaceous Jehol Group, northeastern China. Issue 1 (2nd January 2020) - Cao, Hansheng; He, Wentong
ABSTRACT: The Jehol Biota represents an important phase in the history of biological evolution on Earth. Two sites with Aptian Jehol Biota, located in western Liaoning Province and in northern Hebei Province, northeastern China, have generated a major debate about the relationships between their fossil-bearing layers, resulting in confusions about their stratigraphic correlation and biogenetic sequence. We have applied carbon isotope analysis of total organic carbon to provide new data relevant to this debate and have re-examined the connection between volcanism and carbon cycle perturbations, with consideration of the paleoenvironmental conditions. The rare earth element data show that the provenances of the Jehol Group in western Liaoning and northern Hebei were similar and derived mainly from the underlying andesite. Constrained by the radiometric age, the δ 13 Corg curve suggests that the Dadianzi Formation in northern Hebei is comparable to the three lacustrine layers of the Yixian Formation (ranging from the Jianshangou Bed to the Jingangshan Bed) in western Liaoning. These layers are highly correlated with the early Aptian marine sequence in Oceanic Anoxic Event 1a (OAE 1a), implying that a possible teleconnection (possibly related to a large igneous province) existed between oceanic and terrestrial realms. We also propose that the Xiguayuan Formation above the Dadianzi Formation in northern Hebei is equivalent to the Huanghuashan Breccia Bed at the top of the Yixian Formation in western Liaoning. Moreover, the δ 13 Corg and element geochemical data suggest that the carbon cycle perturbation and the paleolimnological environments were distinctly influenced by the effects of volcanic CO2 during the early Aptian.